Morpho-Syntactic Expansions in Translation from English into Slovenian as a Prototypical Response to the Complexity of the Original - Milojevic Sheppard, Milena (1993)
This work deals with the morpho-syntactic expansions which occur in translation from English into Slovenian, proceeding from the assumption that such expansions are the most common, "prototypical" response of the translator when faced by an original containing grammatically complex structures.